Ferilizer responses in mature Hevea under Sri Lankan conditions - Yogaratnam, N.; Weerasuriya, S.M. (Rubber Research Institute. Agalawatte, 1984)
The results of three out of a series of eight experiments that have been in progress (most of them) since 1976, are discussed. Yield increases in the existing plantations could be obtained with increased applications of nitrogen fertilizers in the form of urea. The level of application could be increased to double that of the currenly recommended rate. Some yield increases were also obtained with applications of potassium. It has also been shown that application of rock phosphate to mature rubber trees is not always benificial. Similary, applications of magnesium containing fertilizers to mature rubber should not also be made indiscriminately. Although the leaf K concentration showed K deficiency in one experiments, application of potassium has increased the K may have to be clone specific and at least for the clone RRIC 45, the leaf K levels may have to be reviced. In general, fertilizer application to mature rubber with complete NPKMg mixtures, may not be economically justified, particular ly in the present context of fertilizers and rubber price. The results reported have covered only parts of the planting cycles following fertilizers application. The experiments are still in progress and will be continued at least until the responses have stabilized. A detailed economic analysis at the end of this period would then give a more realistic picture on the economics of fertilizer application for mature rubber under Sri Lankan agro-climatic conditions
Keywords: Agriculture; Potassium; Phosphorus; Magnesium; Plant nutrition; Yield; Nitrogen; Soil analysis